Rifting Processes at a Continent‐Ocean Transition Rift Revealed by Fault Analysis: Example of Dabbahu‐Manda‐Hararo Rift (Ethiopia). Issue 1 (15th January 2019) - Dumont, S.; Klinger, Y.; Socquet, A.; Escartín, J.; Grandin, R.; Jacques, E.; Medynski, S.; Doubre, C.
Abstract: Analyses of fault attributes have contributed to unraveling fault growth processes in diverse tectonic settings. By integrating such analysis at the scale of a fault population, we propose to investigate the characteristics of a rift that has evolved up to a stage typical of a continent‐ocean transition. We address this problem by considering Dabbahu‐Manda‐Hararo (DMH) rift segment (Central Afar, Ethiopia), recognized for being in a late rifting stage. We quantify fault azimuth, length, and throw attributes for 668 normal faults. Along DMH rift, the mean fault density is 0.87 ± 0.7 km/km 2 and the median tectonic strain ranges from 1.8% to 3.1% assuming a fault dip of 60° and 45°, respectively. Maximum tectonic strain (>10%) is found where the rift azimuth changes. Along‐rift variations in fault azimuth, length, and scaling relationships suggest a different stage of rifting in the northern part of the rift. We show that this difference can be attributed to the influence of the Dabbahu volcano located at the northern tip of the rift, which captured the propagating Manda‐Hararo rift in the last 100 kyr. The morpho‐tectonic analysis reveals numerous common features with slow‐spreading ridge segments, such as the Lucky Strike segment located along the Mid‐Atlantic ridge (segment length, spreading rate, associated magmatic system) but also with intermediate and fast ones (axial valley, fault throws, and diking). This study reveals that a rift at the continent‐ocean transition may be characterized by a transient and evolutionary behavior that shares features with oceanic ridges from slow‐ to fast‐spreading rates. Plain Language Summary: East Africa forms one of the best locations around the world for studying rifting processes. In the Afar depression, three limits of tectonic plates meet to break up the African continent. Faults and volcanism shape rift morphology, and they both participate in the continental breakup. We study 668 faults along the Dabbahu‐Manda‐Hararo rift that is close to give birth to an ocean. We focus on how faults develop by measuring their length, their height, orientation, and number in a given area. Our analysis shows that in the northern part of the rift, faults develop in a singular way, illustrated by their unusual great length at the rift axis. We gather evidences of the specificity of faults located in this area, and we link them to the presence of Dabbahu volcano that developed 100 kyr ago in this area. We also compare our rift to a slow oceanic ridge located in Atlantic with which it shares numerous features (spreading rate, morphology, and magmatic system). This comparison leads us to discuss how different these extensional systems are and to better understand the transition between a continent and an ocean. Key Points: Fault analysis, density map, and strain analysis are performed for 668 normal faults Magmato‐tectonic evolution of the rift is proposed for the last 100 kyr Rift‐ocean ridges are compared to unravel the behavior of a continent‐ocean transition rift